2020
DOI: 10.1177/0883073820974855
|View full text |Cite
|
Sign up to set email alerts
|

Early Implantation as a Main Predictor of Response to Vagus Nerve Stimulation in Childhood-Onset Refractory Epilepsy

Abstract: Objective: We describe a multicenter experience with vagus nerve stimulator implantation in pediatric patients with drug-resistant epilepsy. Our goal was to assess vagus nerve stimulation efficacy and identify potential predictors of favorable outcome. Methods: This is a retrospective study. Inclusion criteria: ≤18 years at time of vagus nerve stimulator implantation, at least 1 year of follow-up. All patients were previously found to be unsuitable for an excisional procedure. Favorable clinical outcome and ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…We did not find any significant difference in age at implantation between the two groups (p ¼ 0.64), but epilepsy duration was significantly shorter in the SR group (p ¼ 0.032). Similar results were published recently by Russo et al 17,18 They studied nearly 90 pediatric patients and reported that the only variable significantly predicting favorable outcomes in children was a shorter time from epilepsy onset to VNS device implantation. 17 Jain and Arya performed a metaanalysis of 101 previous studies and concluded that a shorter duration of epilepsy before VNS implantation was associated with a significantly higher response rate at 1 year.…”
Section: Age At Vns Device Implantation and Epilepsy Durationsupporting
confidence: 87%
See 2 more Smart Citations
“…We did not find any significant difference in age at implantation between the two groups (p ¼ 0.64), but epilepsy duration was significantly shorter in the SR group (p ¼ 0.032). Similar results were published recently by Russo et al 17,18 They studied nearly 90 pediatric patients and reported that the only variable significantly predicting favorable outcomes in children was a shorter time from epilepsy onset to VNS device implantation. 17 Jain and Arya performed a metaanalysis of 101 previous studies and concluded that a shorter duration of epilepsy before VNS implantation was associated with a significantly higher response rate at 1 year.…”
Section: Age At Vns Device Implantation and Epilepsy Durationsupporting
confidence: 87%
“…Similar results were published recently by Russo et al 17,18 They studied nearly 90 pediatric patients and reported that the only variable significantly predicting favorable outcomes in children was a shorter time from epilepsy onset to VNS device implantation. 17 Jain and Arya performed a metaanalysis of 101 previous studies and concluded that a shorter duration of epilepsy before VNS implantation was associated with a significantly higher response rate at 1 year. 19 We agree with their proposal that early referral may be a modifiable factor for desirable seizure outcomes with VNS 19 and early implantation (e.g., within 5 years after seizure onset 17,18 ) may be preferable.…”
Section: Age At Vns Device Implantation and Epilepsy Durationsupporting
confidence: 87%
See 1 more Smart Citation
“…Some case reports supported positive improvements with VNS on autistic behavior in children with DRE and comorbid ASD (20,21), while other studies have reported the opposite effects (22,23). Although several studies have observed that the effect of VNS on autistic behavior are independent of seizure control (21-23), within 2 years of VNS implantation, the proportion of pediatric DRE responders (≥50% reduction in seizure frequency) gradually increases from 20 to 60% (24)(25)(26)(27). Subsequently, the efficacy of VNS tends to stabilize (27)(28)(29).…”
Section: Introductionmentioning
confidence: 98%
“…Non-lesional epilepsy and generalized seizure type were found associated with greater VNS efficacy but with a very modest odds ratio, 13 while the role of age remains debated. 12 , 70 - 72 Several neurophysiological and neuroimaging predictors are being investigated but are not yet validated in clinical practice. 73 - 76 Similarly, we lack biomarkers to predict response to ANT-DBS, with some reports suggesting the potential value of temporal theta-band desynchronization, 77 hippocampal-evoked potentials, 78 and increased functional connectivity between ANT and the default mode network.…”
Section: Areas For Future Researchmentioning
confidence: 99%